THE ACCOMPANIMENT OF SUPPLEMENTARY FOOD FOR MONITORING THE STUNTING RISK CHILDREN IN RENGAS I VILLAGE OGAN ILIR - Ghiffari, Ahmad; Asmalia, Resy; Julia Liona Putria, Sinta; Azhara, Alya; Artanto, Ardi; Utama, Budi; Anisa Suardin, Lucille; Pamudji, Raden; Bagus Setiawan, Rifqi; Saputra, Amja (Universitas Airlangga, 2024)
Introduction: The Ogan Ilir Regency district has the second-highest prevalence of stunting in South Sumatra, with a prevalence rate of 24.9%. Providing additional meals (PMT) is an essential component, especially to improve the conditions of low-income communities affected by malnutrition, with a specific focus on young children. The purpose of the activity is to provide a continuous supply of food, thus preventing body weight loss and promoting optimal nutritional well-being. Methods: The event took place at a village in Payaraman District situated in Ogan Ilir Regency. The participant were the two children, namely Anak R (3.5 years old) and Anak S (1.7 years). The service methods included the process of meal preparation for PMT and the delivery of meals to the homes of children. The method used for the PMT involved the daily allocation of food, the nutrient composition of various foods, including pumpkin, potatoes, carrots, maize and similar substitutes. At the end of the month, the final anthropometric measurements were collected. The anthropometric measurements encompassed body weight, and height. The weight of the youngster was measured using a digital scale manufactured for further analysis. Results: There was a noticeable improvement in weight and height of Anak R and Anak S. Anak R demonstrated a weight gain after the programme from exactly 9.30 kg to 9.80 kg, while Anak S showed an increased weight from 7.80 kg to 8.50 kg. Anak R's height improved from 81.0 cm to 85.0 cm and Anak S's from 71.0 cm to 72.0 cm. Despite the observed growth in the weight and height of both children, the acquired findings did not meet the desired levels for each child's weight and height. Conclusion: Community service activities include food supplementary accompaniment and stunting surveillance has assisted for children with high risk of stunting conditions to gain weight and height after food additions. The accompaniment community service activity can be used as an effort to reduce cases of malnutrition.